Data Transmission Method of a Wireless Digital Microwave Communication System Based on the Zigzag Permutation Algorithm - Yin, Liwei (2021 IEEE International Conference on Industrial Application of Artificial Intelligence (IAAI), 2021)
Aiming at the problem that the redundancy of redundant coded data packets in data transmission affects the performance of long-distance communication, a data transmission method of a wireless digital microwave communication system is proposed based on a zigzag replacement algorithm. A wireless digital microwave communication multichannel network was built to improve the maximum polling capacity of the system under the same system refresh cycle. The sampling nodes in the network system are reasonably clustered, the idea of token communication is introduced into the cluster, and a multichannel invisible token transmission mechanism is designed to reduce the transmission times of data communication. The channel coding and decoding scheme is established based on the zigzag replacement algorithm to reduce the redundancy of redundant coded data packets. The available information of the node is transmitted downward through a DIO message to realize the data transmission of wireless digital microwave communication. Taking the test distance of 5000 m as an example, the packet loss rate of the data transmission method designed in this paper is 9.3%, which is 4.8% and 5.9% lower than that of the communication system based on dynamic label information update and spatial autocorrelation, respectively. Therefore, it can still maintain stable communication performance in long-distance communication.